Regulation of connexin 43 by interleukin 1β in adult rat cardiac fibroblasts and effects in an adult rat cardiac myocyte: fibroblast co-culture model. Issue 1 (January 2020) - McArthur, Lisa; Riddell, Alexandra; Chilton, Lisa; Smith, Godfrey L.; Nicklin, Stuart A.
Abstract: Connexin 43 expression (Cx43) is increased in cardiac fibroblasts (CFs) following myocardial infarction. Here, potential mediators responsible for increasing Cx43 expression and effects of differential CF phenotype on cardiac myocyte (CM) function were investigated. Stimulating adult rat CFs with proinflammatory mediators revealed that interleukin 1β (IL-1β) significantly enhanced Cx43 levels through the IL-1β pathway. Additionally, IL-1β reduced mRNA levels of the myofibroblast (MF) markers: (i) connective tissue growth factor (CTGF) and (ii) α smooth muscle actin (αSMA), compared to control CFs. A co-culture adult rat CM:CF model was utilised to examine cell-to-cell interactions. Transfer of calcein from CMs to underlying CFs suggested functional gap junction formation. Functional analysis revealed contraction duration (CD) of CMs was shortened in co-culture with CFs, while treatment of CFs with IL-1β reduced this mechanical effect of co-culture. No effect on action potential rise time or duration of CMs cultured with control or IL-1β-treated CFs was observed. These data demonstrate that stimulating CFs with IL-1β increases Cx43 and reduces MF marker expression, suggesting altered cell phenotype. These changes may underlie the reduced mechanical effects of IL-1β treated CFs on CD of co-cultured CMs and therefore have an implication for our understanding of heterocellular interactions in cardiac disease. Abstract : Cell biology; Molecular biology; Cell culture; Membrane; Inflammation; Gene expression; Cardiovascular system; Myofibroblast; Inflammation; Heterocellular coupling; Cardiac myocyte contraction; Action potential